Effect of transcranial magnetic stimulation on rectal sensitivity in irritable bowel syndrome: a randomized, placebo‐controlled pilot study. (March 2014) - Melchior, C.; Gourcerol, G.; Chastan, N.; Verin, E.; Menard, J. F.; Ducrotte, P.; Leroi, A. M.
Abstract Aim Repetitive transcranial magnetic stimulation (rTMS) applied to the motor cortex can induce analgesic effects in patients with chronic pain syndromes through its effect on central pain‐modulatory systems. Our aim was to evaluate the effect of rTMS on rectal sensitivity in irritable bowel syndrome (IBS) patients. Method In this randomized, sham‐controlled, proof‐of concept trial, 21 IBS patients (11 women and 10 men; mean age 44.0 ± 12.6 years) were randomized, using a double‐blind crossover protocol, to active or sham rTMS for 5 days of treatment. The primary outcome was the increase in the pressure pain threshold after rTMS. Secondary outcomes were the changes in maximum tolerated rectal volume, rectal compliance and average pain intensity between baseline and the end of the treatments. Results There were no statistically significant differences between active and sham rTMS in terms of an increase in the pressure pain threshold, maximum tolerated volume and rectal compliance at the end of the treatments compared with baseline. However, in the subgroup of patients with the most marked rectal hypersensitivity, the volume threshold was significantly improved by active, but not by sham, rTMS (P = 0.03). Patients experienced a significant improvement in pain regardless of the type of stimulation. Conclusion This pilot study failed to demonstrate any benefit of rTMS on our primary end‐point. However, the effect of rTMS on rectal tolerated volume in the most hypersensitive patients was encouraging enough to plan more powered studies.